Identitas Kristiani yang Berakar dalam Keyahudian: Berdasarkan Studi atas Pentakosta sebagai Kelahiran Gereja - Stenly Vianny Pondaag (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2023)
The article deals with an important issue in Christianity, namely the root of Christianity in Judaism. The issue presupposes a theological relationship between Christianity and Judaism, or between the Church and the Synagogue. As a starting point of the study, the author tries to examine the meaning of the Pentecost that connects Christianity and Judaism. In this regard, the main question is how to explain the identification of Pentecost as the beginning of the Church. One of the main findings of this study is that the identification of Pentecost as the beginning of the Church is closely related to the celebration of the Seven Weeks in the Jewish tradition as the root of Pentecost. Suppose the Jews view the Sinai event as the beginning of their formation as God's people. In that case, the Feast of Seven Weeks or Pentecost is also an opportunity for them to commemorate the formation of Israel as God's people. Moreover, the article offers an important consideration regarding the dialogue between Christianity and Judaism. The encounter between Christianity and Judaism is not understood merely as an external issue in the context of interreligious dialogue, but rather as a profound matter of Christian identity. If the Church wants to reflect on itself and its own identity, then the Church will automatically speak about Judaism. In Judaism, the Church finds the roots and basis of her identity.